Extended theory of planned behavior in explaining the intention to COVID-19 vaccination uptake among mainland Chinese university students: an online survey study - Fan, Chia-Wei; Chen, I-Hua; Ko, Nai-Ying; Yen, Cheng-Fang; Lin, Chung-Ying; Griffiths, Mark D.; Pakpour, Amir H. (Human vaccines & immunotherapeutics, 2021)
Objective: The Theory of Planned Behavior (TPB) is one of the most robust models in explaining health-related behavior. In this study, we tested the extended TPB to predict university students' intentions to uptake COVID-19 vaccination. Methods: An online cross-sectional survey was developed to investigate students' intention to uptake the COVID-19 vaccine based on the components of the TPB (i.e., attitude, subjective norms, and perceived behavioral control) and extended components (i.e., knowledge about COVID-19, risk perception of COVID-19, and past influenza vaccination behavior). Non-probability sampling was used to collect data from 3145 students from 43 universities in mainland China in January 2021. Structural equation modeling (SEM) was applied to examine the proposed model. Enrolled students were relatively young (mean age = 20.80 years; SD = 2.09), half of them are female (50.2%), and most of them were studying in undergraduate programs (n = 3026; 96.2%). Results: The results showed that students' knowledge of the COVID-19 vaccine and risk perception of COVID-19 positively influenced their attitude toward the uptake of a COVID-19 vaccine. Also, students' attitude toward COVID-19 vaccination uptake and their past influenza vaccination uptake behaviors were positively associated with the intention to uptake COVID-19 vaccination. Subjective norm and perceived behavioral control were not significant predictors for the intention to uptake COVID-19 vaccination (R 2 = 0.49). Conclusions: The present study demonstrated that the extended TPB appears to be an efficient model with the focus on attitude, knowledge, risk perception, and past influenza vaccination uptake behaviors in explaining students' intention for COVID-19 vaccination.